Preparation method of gallium-indium alloy doped aluminum vanadium oxide hydrate positive electrode

By introducing gallium-indium alloy and aluminum ion co-doping into aluminum vanadium oxide cathode materials, the problems of poor conductivity and insufficient structural stability of vanadium-based cathode materials in aqueous zinc-ion batteries have been solved, realizing the preparation of high-performance cathode materials with excellent electrochemical performance and long cycle life.

CN120914192APending Publication Date: 2025-11-07INNER MONGOLIA UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510987847.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing vanadium-based cathode materials suffer from poor conductivity, slow ion diffusion, and insufficient structural stability in aqueous zinc-ion batteries.

Method used

A method for preparing a gallium-indium alloy-doped aluminum vanadium oxide hydrate positive electrode was adopted. By introducing gallium-indium alloy and aluminum ions into aluminum vanadium oxide for co-doping, a continuous electron transport channel was constructed and the ion diffusion path was broadened, thereby enhancing the electron/ion transport capability and structural stability of the material.

Benefits of technology

It significantly improves the conductivity and ion migration capability of the cathode material, extends cycle life, achieves high specific capacity and excellent rate performance, and adopts a green and simple preparation process suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120914192A_ABST
    Figure CN120914192A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a gallium-indium alloy doped aluminum vanadium oxide hydrate positive electrode, which adopts a novel modification strategy of synergistic doping of gallium-indium alloy and aluminum ions, and systematically improves the electrochemical performance of a vanadium oxide positive electrode material in an aqueous zinc ion battery. Due to the introduction of the GaIn alloy, the electronic conductivity of the material is remarkably enhanced, a continuous electron transmission path is formed, and the interface resistance is effectively reduced; the doping of Al < 3 + > ions regulates and controls the crystal structure, widens the ion diffusion channel, improves the migration rate of Zn < 2 + >, enhances the capacity retention capability and long-period stability of the material under high magnification, and has a very good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary battery technology, specifically to a method for preparing a gallium-indium alloy-doped aluminum vanadium oxide hydrate positive electrode. Background Technology

[0002] The increasingly severe environmental problems, especially the challenges posed by fossil fuel combustion, have accelerated the research and development of efficient and green energy storage technologies. Although lithium-ion batteries dominate portable electronic devices, their inherent resource limitations, safety risks, and the environmental burden of organic electrolytes have prompted the research community to focus on alternative energy storage systems. Aqueous zinc-ion batteries (AZIBs), with their inherent safety (aqueous electrolyte), abundant resources (zinc), environmental friendliness, and considerable theoretical capacity, have shown great potential in large-scale energy storage applications. However, a key bottleneck in their commercialization lies in developing high-performance cathode materials.

[0003] Vanadium-based oxides (such as V₂O₅ and VO₂) are considered highly attractive cathode materials for AZIBs due to their low cost, simple synthesis, high specific capacity (due to multi-electron redox reactions), and open layered structure. For example, patent CN112635746A discloses a method for preparing vanadium-based cathode materials for aqueous zinc-ion batteries. The vanadium oxide cathode material prepared by this invention exhibits good zinc storage performance, maintaining a discharge specific capacity of 205 mAh / g after 2000 charge-discharge cycles at a high current density of 10 A / g. Patent CN 111573731A discloses a hydrothermal method for preparing magnesium-ion pre-intercalated hydrated vanadium pentoxide nanowire zinc-ion battery cathode materials. The electrode material prepared by this invention has an initial discharge specific capacity of 145.9 mAh / g at a current density of 5 A / g. -1 After 2000 cycles, its capacity retention rate exceeded 91%. The above reports demonstrate the feasibility of vanadium oxide cathode materials for zinc storage. However, vanadium oxide cathode materials suffer from low conductivity, slow solid-state diffusion kinetics, and poor structural stability when used in aqueous zinc-ion batteries, severely limiting the development of zinc-ion batteries. Summary of the Invention

[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of this invention is to provide a method for preparing magnesium vanadate salt and its application, so as to solve the problems of poor conductivity, slow ion diffusion and insufficient structural stability of vanadium-based cathode materials prepared by the prior art when used in aqueous zinc-ion batteries.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0006] A preparation method of a gallium-indium alloy doped aluminum vanadium oxide hydrate positive electrode, comprising the following steps:

[0007] Step 1: Vanadium pentoxide is added into an ethanol solution to obtain a solution A; in the solution A, the concentration of vanadium pentoxide is 0.03-0.1 mol / L; the ethanol solution is prepared from anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is 1:1.

[0008] Step 2: H2O2 is added into the solution A in step 1, and the reaction is continuously stirred to completely pyrolyze vanadium pentoxide; wherein the amount of H2O2 added is 3-7 mL;

[0009] Step 3: Aluminum chloride is added into an ethanol solution to obtain a solution C; in the solution C, the concentration of aluminum chloride is 0.05-0.2 mol / L;

[0010] Step 4: The solution C is added into the solution B, and the stirring is continuously performed for 2-4 hours to obtain a solution D; wherein the volume ratio of the solution C to the solution B is 1:(2-5);

[0011] Step 5: The solution D obtained in step 4 is reacted at 160-200°C for 12-35 hours, and the reaction product is obtained after natural cooling and filtration;

[0012] Step 6: The reaction product obtained in step 5 is washed multiple times and dried to obtain aluminum-doped hydrated V2O5 powder; the aluminum-doped hydrated V2O5 powder, conductive carbon black and polyvinylidene fluoride are uniformly mixed, and N-methyl pyrrolidone is added to form a slurry; wherein the mass ratio of the aluminum-doped hydrated V2O5 powder, the conductive carbon black and the polyvinylidene fluoride is 7:2:1;

[0013] Step 7: A gallium-indium alloy dispersion liquid is added into the slurry obtained in step 6, and the slurry is coated on a current collector after being fully ground, and the positive electrode is obtained after drying.

[0014] Preferably, in the solution A of step 1, the concentration of vanadium pentoxide is 0.04-0.07 mol / L.

[0015] Preferably, in step 2, the amount of H2O2 added is 4-6 mL per 1 g of vanadium pentoxide; and the concentration of H2O2 is 30% according to the mass percentage.

[0016] Preferably, in the solution C of step 3, the concentration of aluminum chloride is 0.08-0.15 mol / L.

[0017] Preferably, in step 5, the reaction temperature is 180°C, and the reaction time is 24 hours.

[0018] Preferably, in step 7, the grinding time is 10-15 min, and the current collector is a metal titanium foil; the gallium-indium alloy dispersion liquid is obtained by the following steps:

[0019] The gallium-indium alloy is added to ethanol and broken for 5-10 min to obtain the gallium-indium alloy dispersion liquid; wherein, 1 mL of ethanol is prepared for every 3 muL of gallium-indium alloy.

[0020] The application also provides an application of the positive electrode prepared by the preparation method.

[0021] Compared with the prior art, the application has the following beneficial effects:

[0022] 1. The application innovatively proposes and successfully realizes the introduction of gallium-indium alloy (GaIn) and aluminum ions (Al 3+ ) into vanadium pentoxide (V2O5) to construct a new type of co-doped vanadium oxide positive electrode material (GaIn-HAVO); the introduction of GaIn effectively constructs a continuous electron transmission channel, significantly improving the electrical conductivity; Al 3+ , widens the ion diffusion path and stabilizes the crystal structure through lattice embedding, thereby synergistically improving the electronic / ionic transport capacity and structural stability of the material; this synergistic mechanism is not simply additive, but forms a strong coupling effect in terms of electrical conductivity, ion migration and structural stability, which is the key to the essential leap in the performance of the positive electrode material; ultimately, through the synergistic doping of GaIn alloy and Al 3+ ions, the multi-dimensional performance of the positive electrode material is improved.

[0023] 2. After further research on the prepared positive electrode material, it is found that through the high wettability of GaIn alloy and the "lattice support" effect of Al 3+ ions, the volume expansion stress and vanadium dissolution problems of the material during charging and discharging are effectively alleviated, and a high-stability electrode / electrolyte interface and internal lattice system are constructed, which enables the positive electrode material to maintain a capacity retention rate of more than 85% after 10000 cycles at a high current density of 5A·g -1 , which is significantly better than traditional vanadium-based positive electrode materials, thereby realizing ultra-long cycle life and excellent rate performance through dual regulation of the interface and crystal structure, and exhibiting extremely high application value.

[0024] 3. The preparation method is a low-temperature, non-toxic, solution process combined with a simple one-pot hydrothermal synthesis strategy, which realizes the green controllability of the whole process from raw material pretreatment, co-doping to slurry preparation and electrode forming, avoids organic solvent pollution and high-energy consumption heat treatment, constructs a green synthesis process system that can be scaled up, and is very suitable for industrial scale expansion. BRIEF DESCRIPTION OF DRAWINGS

[0025] Figure 1 XRD analysis chart of GaIn-HAVO material prepared for the embodiment 1 of the present application.

[0026] Figure 2 SEM chart of GaIn-HAVO material prepared for the embodiment 1 of the present application.

[0027] Figure 3 Rate performance chart of zinc ion battery positive electrode GaIn-HAVO prepared for the embodiment 1 of the present application.

[0028] Figure 4 Long cycle chart of zinc ion battery positive electrode GaIn-HAVO prepared for the embodiment 1 of the present application at 5Ag -1 current density.

[0029] Figure 5 XRD analysis chart of GaIn-HAVO material prepared for the embodiment 2 of the present application.

[0030] Figure 6 Long cycle chart of zinc ion battery positive electrode HAVO prepared for the comparative example 1 at 5Ag -1 current density.

[0031] Figure 7 Long cycle chart of zinc ion battery positive electrode VOH prepared for the comparative example 2 at 5Ag -1 current density. DETAILED DESCRIPTION

[0032] The present application will be further described below in conjunction with the drawings and embodiments.

[0033] Those skilled in the art shall know that the detailed description is only used for illustrating and explaining the present application, and is not used for limiting the present application. Therefore, the above-mentioned embodiments can be replaced and changed without departing from the spirit and scope of the claims.

[0034] One kind of preparation method of gallium-indium alloy doped aluminum vanadium oxide hydrate positive electrode

[0035] Step 1: Vanadium pentoxide is added into ethanol solution to obtain solution A; in the solution A, the concentration of vanadium pentoxide is 0.03mol / L-0.1mol / L; the ethanol solution is prepared by anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is 1:1.

[0036] Step 2: Add H2O2 to the solution A in step 1, continue to stir the reaction to completely pyrolyze vanadium pentoxide; wherein, the amount of H2O2 added is 3-7 mL;

[0037] Step 3: Add aluminum chloride to the ethanol solution to obtain solution C; in the solution C, the concentration of aluminum chloride is 0.05 mol / L-0.2 mol / L;

[0038] Step 4: Add solution C to solution B, continue to stir for 2-4 hours to obtain solution D; wherein, the volume ratio of solution C and solution B is 1:(2-5);

[0039] Step 5: React the solution D obtained in step 4 at 160-200 DEG C for 12-35 hours, and filter the reaction product after natural cooling;

[0040] Step 6: After washing and drying the reaction product filtered in step 5 for multiple times, aluminum-doped hydrated V2O5 powder is obtained; the aluminum-doped hydrated V2O5 powder, conductive carbon black and polyvinylidene fluoride are mixed uniformly, and N-methyl pyrrolidone is added to form a slurry; wherein, the mass ratio of aluminum-doped hydrated V2O5 powder, conductive carbon black and polyvinylidene fluoride is 7:2:1;

[0041] Step 7: Add gallium-indium alloy dispersion liquid to the slurry obtained in step 6, grind thoroughly, and then coat the obtained slurry on a current collector to obtain the positive electrode after drying.

[0042] The present application aims at the common technical bottleneck of current vanadium-based positive electrode materials in poor conductivity, slow ion diffusion and insufficient structural stability, and conceives to improve the performance by doping other elements; but at the same time, it is considered that doping may affect the stability of the material. In order to solve the two technical problems at the same time, the present application proposes an innovative material modification strategy: introducing gallium-indium alloy (GaIn) into aluminum vanadium oxide hydrate (HAVO) for doping regulation to construct a high-performance aqueous zinc ion battery positive electrode material; on this basis, aluminum ions are introduced to participate in the construction of vanadium oxygen skeleton, and the structural stability of the material is enhanced by doping aluminum elements. For this purpose, the present application adjusts the preparation method and successfully prepares a gallium-indium alloy-doped aluminum vanadium oxide hydrate positive electrode. At the same time, the positive electrode material obtained based on the conception of the present application has unexpected performance advantages: the GaIn alloy can form a continuous conductive network on the surface and internal interface of the material due to its excellent electronic conductivity and room temperature flowability, which significantly improves the overall electronic transmission efficiency of the electrode and optimizes the interface compatibility between the electrode and the electrolyte, effectively relieving the volume expansion stress generated during charging and discharging. At the same time, the aluminum element participates in the doping of the vanadium oxygen skeleton in the form of A 3+ , which expands the Zn 2+The diffusion channels in the material reduce the migration energy barrier and accelerate the ion transmission kinetics process; in addition, Al 3+ The embedding in the crystal lattice also enhances the structural stability of the material, plays a role of spatial "support", and effectively inhibits the structural collapse and vanadium dissolution in the cycle. The complex effect of GaIn and Al 3+ The synergistic effect not only realizes multiple optimization at the microstructure level, but also breaks through the performance limitation of traditional vanadium oxide positive electrode materials through multiple dimensions such as conductivity improvement, ion channel expansion, interface stability enhancement, and crystal framework strengthening. The strategy designed in the present application integrates interface engineering and crystal structure regulation, and has a significant synergistic strengthening effect. Therefore, the doped aluminum vanadium oxide hydrate positive electrode material exhibits excellent rate performance and ultra-long cycle life while maintaining high specific capacity, and still has excellent capacity retention rate at high current density. More importantly, the material is prepared by a green, simple and controllable one-pot hydrothermal method, has the advantages of cheap raw materials, stable process and suitability for large-scale expansion, and meets the comprehensive requirements of safety, economy and environmental friendliness for current large-scale energy storage technology, and has wide application prospect and industrialization value.

[0043] In some embodiments of the present application, in solution A of step 1, the concentration of vanadium pentoxide is 0.03-0.1 mol / L, and further preferably 0.04 mol / L-0.07 mol / L. The regulation of the concentration of vanadium pentoxide affects the initial concentration and ratio state of the reaction precursor, and then affects the phase structure and crystallinity of the generated product. If the concentration of vanadium pentoxide is lower than 0.03 mol / L, it will lead to insufficient participation of reactants, insufficient development of product structure, and affect its specific capacity and cycle stability; while the concentration of vanadium pentoxide is higher than 0.1 mol / L, it will lead to the generation of by-products or the formation of agglomerated structure, increase the particle size, limit the ion migration channel, and thus reduce the battery performance. Therefore, the concentration of vanadium pentoxide can be 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L, or in a numerical range constituted by any two specific numerical values as endpoints; it should be understood that in the embodiments, any of the above ranges can be combined with any other range.

[0044] In some embodiments of the present application, in step 2, 4-6 mL of H2O2 is added per 1 g of vanadium pentoxide. The H2O2 is hydrogen peroxide solution, and the concentration of H2O2 in the added hydrogen peroxide solution is 30% according to the mass percentage.

[0045] In some embodiments of the present application, in step 3, the concentration of aluminum chloride in solution C is 0.05-0.2 mol / L, and is further preferably 0.08-0.15 mol / L; therefore, the concentration of aluminum chloride can be 0.05 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.11 mol / L, 0.12 mol / L, 0.13 mol / L, 0.14 mol / L, 0.15 mol / L or 0.2 mol / L, or in a numerical range formed by any two of the above specific numerical values as endpoints; it should be understood that in the embodiments, any of the above ranges can be combined with any other range.

[0046] In some embodiments of the present application, in step 5, the reaction temperature is 180°C, and the reaction time is 24 h.

[0047] In some embodiments of the present application, in step 7, the grinding time is 10-15 min, and the current collector is a metal titanium foil; the gallium-indium alloy dispersion liquid is obtained by the following steps:

[0048] The gallium-indium alloy is added to ethanol, and broken for 5-10 min to obtain the gallium-indium alloy dispersion liquid; wherein 3 μL of gallium-indium alloy is prepared with 1 mL of ethanol.

[0049] II. Use of the positive electrode material prepared by the above preparation method

[0050] The positive electrode material is used for the preparation of aqueous zinc ion batteries, lithium ion batteries, sodium ion batteries, calcium ion batteries and magnesium ion batteries.

[0051] III. Examples and comparative examples

[0052] Example 1

[0053] (1) Vanadium pentoxide (V2O5, 2 mmol) is added to a mixed solution of 15 mL of anhydrous ethanol and 15 mL of deionized water, and is uniformly mixed and stirred by strong stirring, and is recorded as solution A;

[0054] (2) 5 mL of 30% hydrogen peroxide solution is added to solution A, and magnetic stirring is continued for 0.5 h, and is recorded as solution B;

[0055] (3) Aluminum chloride hexahydrate (AlCl3·6H2O, 3 mmol) is added to a mixed solution of 5 mL of anhydrous ethanol and 5 mL of deionized water, and stirring is continued until complete dispersion, and is recorded as solution C;

[0056] (4) Solution C is added to solution B, and is recorded as solution D, and strong stirring is continued for 3 h;

[0057] (5) Transfer solution D to a 100 mL polytetrafluoroethylene-lined high-pressure reaction kettle and place it in a blast drying oven at 180°C for 24 h;

[0058] (6) After the reaction is completed, cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol 3 times, and dry in a vacuum drying oven at 80°C for 12 h to obtain a HAVO powder sample;

[0059] (7) Mix the HAVO powder obtained in step (6), conductive carbon black, and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1 into 0.7 mL of N-methyl pyrrolidone (NMP) solution to form a slurry;

[0060] (8) Add a dispersion liquid of gallium-indium alloy at a ratio of 4:1 to the slurry formed in step (7), grind for 10 min to fully mix the slurry, and coat it on a titanium foil current collector. Place it in an oven for drying to finally obtain a GaIn-HAVO positive electrode.

[0061] Example 2

[0062] (1) Add vanadium pentoxide (V2O5, 2 mmol) to a mixed solution of 15 mL of anhydrous ethanol and 15 mL of deionized water, and mix and stir uniformly, denoted as solution A;

[0063] (2) Add 3 mL of 30% hydrogen peroxide solution to solution A, continue to magnetically stir for 0.5 h, and denoted as solution B;

[0064] (3) Add aluminum chloride hexahydrate (AlCl3·6H2O, 1 mmol) to a mixed solution of 5 mL of anhydrous ethanol and 5 mL of deionized water, continue to stir until fully dispersed, and denoted as solution C;

[0065] (4) Add solution C to solution B, denoted as solution D, and continue to vigorously stir for 3 h;

[0066] (5) Transfer solution D to a 100 mL polytetrafluoroethylene-lined high-pressure reaction kettle and place it in a blast drying oven at 160°C for 24 h;

[0067] (6) After the reaction is completed, cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol 3 times, and dry in a vacuum drying oven at 80°C for 12 h to obtain a HAVO powder sample;

[0068] (7) Mix the HAVO powder obtained in step (6), conductive carbon black, and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 into 0.7 mL of N-methyl pyrrolidone (NMP) solution to form a slurry;

[0069] (8) To the slurry formed in step (7), a dispersion liquid of gallium-indium alloy with a ratio of 4:1 was added, and the slurry was ground for 10 min to mix thoroughly and coated on a titanium foil current collector, and then placed in an oven for drying, to finally obtain a GaIn-HAVO positive electrode.

[0070] Example 3

[0071] (1) Vanadium pentoxide (V2O5, 1.5 mmol) was added to a mixed solution of 15 mL of anhydrous ethanol and 15 mL of deionized water, and uniformly stirred by strong mixing, denoted as solution A;

[0072] (2) 5 mL of 30% hydrogen peroxide solution was added to solution A, and magnetic stirring was continued for 0.5 h, denoted as solution B;

[0073] (3) Aluminum chloride hexahydrate (AlCl3·6H2O, 3 mmol) was added to a mixed solution of 5 mL of anhydrous ethanol and 5 mL of deionized water, and stirring was continued until complete dispersion, denoted as solution C;

[0074] (4) Solution C was added to solution B, denoted as solution D, and strong stirring was continued for 3 h;

[0075] (5) Solution D was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reaction kettle, and it was placed in a blast drying oven at 180°C for 24 h;

[0076] (6) After the reaction was completed, it was cooled to room temperature, washed repeatedly with deionized water and anhydrous ethanol for 3 times, and dried in a vacuum drying oven at 80°C for 12 h, to obtain a HAVO powder sample;

[0077] (7) The HAVO powder obtained in step (6), conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a ratio of 7:2:1 to form a slurry in 0.7 mL of N-methyl pyrrolidone (NMP) solution;

[0078] (8) To the slurry formed in step (7), a dispersion liquid of gallium-indium alloy with a ratio of 4:1 was added, and the slurry was ground for 10 min to mix thoroughly and coated on a titanium foil current collector, and then placed in an oven for drying, to finally obtain a GaIn-HAVO positive electrode.

[0079] Example 4

[0080] (1) Vanadium pentoxide (V2O5, 1.2 mmol) was added to a mixed solution of 15 mL of anhydrous ethanol and 15 mL of deionized water, and uniformly stirred by strong mixing, denoted as solution A;

[0081] (2) 5 mL of 30% hydrogen peroxide solution was added to solution A, and magnetic stirring was continued for 0.5 h, denoted as solution B;

[0082] (3) Add aluminum chloride hexahydrate (AlCl3-6H2O, 2 mmol) to a mixed solution of 5 mL of anhydrous ethanol and 5 mL of deionized water, continue to stir until completely dispersed, and mark it as solution C;

[0083] (4) Add solution C to solution B, mark it as solution D, and continue to stir vigorously for 3 h;

[0084] (5) Transfer solution D to a 100 mL polytetrafluoroethylene-lined high-pressure reaction kettle, and place it in a blast drying oven at 180°C for 36 h;

[0085] (6) After the reaction is completed, cool to room temperature, wash repeatedly with deionized water and anhydrous ethanol 3 times, and dry in a vacuum drying oven at 80°C for 12 h to obtain a HAVO powder sample;

[0086] (7) Mix the HAVO powder obtained in step (6), conductive carbon black, and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1 to form a slurry in 0.9 mL of N-methylpyrrolidone (NMP) solution;

[0087] (8) Add a dispersion of gallium-indium alloy with a ratio of 4:1 to the slurry formed in step (7), grind for 20 min to mix the slurry thoroughly, and coat it on a titanium foil current collector, and place it in an oven for drying to finally obtain a GaIn-HAVO positive electrode.

[0088] Example 5

[0089] (1) Add vanadium pentoxide (V2O5, 1 mmol) to a mixed solution of 15 mL of anhydrous ethanol and 15 mL of deionized water, and mix and stir uniformly, and mark it as solution A;

[0090] (2) Add 5 mL of 30% hydrogen peroxide solution to solution A, continue to stir magnetically for 0.5 h, and mark it as solution B;

[0091] (3) Add aluminum chloride hexahydrate (AlCl3-6H2O, 3 mmol) to a mixed solution of 5 mL of anhydrous ethanol and 5 mL of deionized water, continue to stir until completely dispersed, and mark it as solution C;

[0092] (4) Add solution C to solution B, mark it as solution D, and continue to stir vigorously for 3 h;

[0093] (5) Transfer solution D to a 100 mL polytetrafluoroethylene-lined high-pressure reaction kettle, and place it in a blast drying oven at 180°C for 24 h;

[0094] (6) After the reaction is completed, cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol 3 times, and dry in a vacuum drying oven at 80°C for 12h to obtain a HAVO powder sample;

[0095] (7) Mix the HAVO powder obtained in step (6), conductive carbon black, and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1 into 0.7mL of N-methyl pyrrolidone (NMP) solution to form a slurry;

[0096] (8) Add a dispersion liquid of gallium-indium alloy in a ratio of 4:1 to the slurry formed in step (7), grind for 10min to fully mix the slurry, and coat on a titanium foil current collector, and then put into an oven for drying to finally obtain a GaIn-HAVO positive electrode.

[0097] Example 6

[0098] (1) Add vanadium pentoxide (V2O5, 1.8mmol) to a mixed solution of 15mL anhydrous ethanol and 15mL deionized water, and mix and stir uniformly, denoted as solution A;

[0099] (2) Add 5mL of 30% hydrogen peroxide solution to solution A, continue to magnetically stir for 0.5h, denoted as solution B;

[0100] (3) Add aluminum chloride hexahydrate (AlCl3·6H2O, 3mmol) to a mixed solution of 5mL anhydrous ethanol and 5mL deionized water, continue to stir until fully dispersed, denoted as solution C;

[0101] (4) Add solution C to solution B, denoted as solution D, and continue to stir vigorously for 3h;

[0102] (5) Transfer solution D to a 100mL polytetrafluoroethylene-lined high-pressure reaction kettle, and place it in a blast drying oven at 180°C for 24h;

[0103] (6) After the reaction is completed, cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol 3 times, and dry in a vacuum drying oven at 80°C for 12h to obtain a HAVO powder sample;

[0104] (7) Mix the HAVO powder obtained in step (6), conductive carbon black, and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1 into 0.7mL of N-methyl pyrrolidone (NMP) solution to form a slurry;

[0105] (8) Add a dispersion liquid of gallium-indium alloy in a ratio of 4:1 to the slurry formed in step (7), grind for 10min to fully mix the slurry, and coat on a titanium foil current collector, and then put into an oven for drying to finally obtain a GaIn-HAVO positive electrode.

[0106] Comparative Example 1

[0107] Improvements were made on the basis of Example 1, and the difference between them is that no gallium-indium alloy is added. The specific preparation method is as follows:

[0108] (1) Vanadium pentoxide (V2O5, 2 mmol) was added to a mixed solution of 15 mL of anhydrous ethanol and 15 mL of deionized water, and was uniformly stirred by strong mixing, and was recorded as solution A;

[0109] (2) 5 mL of 30% hydrogen peroxide solution was added to solution A, and magnetic stirring was continued for 0.5 h, and was recorded as solution B;

[0110] (3) Aluminum chloride hexahydrate (AlCl3·6H2O, 3 mmol) was added to a mixed solution of 5 mL of anhydrous ethanol and 5 mL of deionized water, and stirring was continued until complete dispersion, and was recorded as solution C;

[0111] (4) Solution C was added to solution B, and was recorded as solution D, and strong stirring was continued for 3 h;

[0112] (5) Solution D was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reaction kettle, and was placed in a blast drying oven at 180°C for 24 h;

[0113] (6) After the reaction was completed, it was cooled to room temperature, washed repeatedly with deionized water and anhydrous ethanol for 3 times, and dried in a vacuum drying oven at 80°C for 12 h, to obtain a HAVO powder sample;

[0114] (7) The HAVO powder sample prepared in step (6), conductive carbon black, and polyvinylidene fluoride (PVDF) were added to an N-methyl pyrrolidone (NMP) solution in a ratio of 7:2:1, and were ground and stirred into a uniform slurry, which was uniformly coated on a titanium foil current collector, and was dried in a vacuum drying oven at 80°C overnight, to obtain a positive electrode sheet.

[0115] Comparative Example 2

[0116] Improvements were made on the basis of Example 1, and the difference between them is that no aluminum ion doping was performed, and no gallium-indium alloy was added. The specific steps are as follows:

[0117] (1) Vanadium pentoxide (V2O5, 2 mmol) was added to a mixed solution of 20 mL of anhydrous ethanol and 20 mL of deionized water, and was uniformly stirred by strong mixing, and was recorded as solution A;

[0118] (2) 5 mL of 30% hydrogen peroxide solution was added to solution A, and magnetic stirring was continued for 2 h, and was recorded as solution B;

[0119] (3) Transfer solution B to a 100 mL polytetrafluoroethylene-lined high-pressure reaction kettle and place it in a blast drying oven at 180°C for 24 h;

[0120] (4) After the reaction is completed, cool to room temperature, wash repeatedly with deionized water and anhydrous ethanol 3 times, and dry in a vacuum drying oven at 80°C for 12 h to obtain a VOH powder sample.

[0121] (5) Add the VOH powder sample prepared in step (4), conductive carbon black, and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1 to an N-methylpyrrolidone (NMP) solution, grind and stir into a uniform slurry, and evenly spread it on a titanium foil current collector. Dry in a vacuum drying oven at 80°C overnight to obtain a positive electrode sheet.

[0122] III. Phase characterization of the prepared product

[0123] The slurry prepared after adding gallium-indium alloy in step (8) of Example 1 and Example 2 was subjected to XRD analysis, obtaining Figure 1 and Figure 5 . As can be seen from Figure 1 , the sample prepared in Example 1 was subjected to X-ray diffraction analysis, and it can be seen that its crystal phase structure is highly similar to that of H 11 Al2V6O 23.2 (PDF #49-0693); the scanning electron microscope image is shown in Figure 2 , and the material exhibits a uniform nanosheet structure. As can be seen from Figure 5 , the sample prepared in Example 2 has a crystal phase structure highly similar to that of H 11 Al2V6O 23.2 (PDF #49-0693), but contains a small amount of VO2·nH2O (PDF #18-1445). Through X-ray diffraction (XRD) analysis, it was found that after doping the HAVO powder with gallium-indium alloy (liquid metal), no significant changes in crystal phase were observed, and no new diffraction peaks appeared. This indicates that during the doping process, the introduction of gallium-indium alloy did not destroy the long-range order of the host lattice of the HAVO powder. A small part of it may only cause subtle distortion of the host lattice, and most of the gallium-indium alloy occupies the defect-rich regions (such as grain boundaries and interlayers) in the powder. This doping form may cause changes in local structure and electronic structure, effectively enhancing the electronic conductivity of HAVO and improving the ion transport path of the electrode, thereby improving the overall electrochemical activity of the electrode.

[0124] IV. Electrochemical performance test

[0125] The positive electrode sheets prepared in the examples and comparative examples were used to assemble zinc-ion batteries, with an active material loading of 2.1–2.5 mg / cm³. -2 In air, a coin cell was assembled using zinc foil as the negative electrode, 3.0 M zinc trifluoromethanesulfonate as the electrolyte, and glass fiber (Whatman, GF / D) as the separator. Its electrochemical performance was tested, with a current density range of 0.1–8.0 Ag. -1 The charge / discharge cutoff voltage is 0.2–1.6V.

[0126] The zinc-ion batteries prepared in the examples and comparative examples were tested, and the following results were obtained:

[0127] (1) Example 1: In 0.1Ag -1 The discharge specific capacity at current density is 378.4 mAh g. -1 When the current density increases to 8Ag -1 At that time, it still had 119.2 mAh g -1 High specific capacity ( Figure 3 ).like Figure 4 As shown, in 5Ag -1 After undergoing long-cycle charge-discharge testing, the initial discharge specific capacity was 132.1 mAh g. -1 After activation, the specific capacity increased to 153.0 mAh g. -1 After 10,000 cycles, it still retains 133.5 mAh g. -1 It has a high specific capacity, with a capacity retention rate of 87.2% compared to the highest specific capacity; and no capacity decay compared to the initial specific capacity.

[0128] (2) Example 2: In 0.1Ag -1 The discharge specific capacity at current density is 287.3 mAh g. -1 In 5Ag -1 Under long-cycle charge-discharge testing, the initial specific capacity was 98.2 mAh g. -1 After 10,000 cycles, the capacity retention rate was 82.4%.

[0129] (3) Example 3: In 0.1Ag -1 The discharge specific capacity at current density is 281.4 mAh g. -1 In 5Ag -1 Under long-cycle charge-discharge testing, the initial specific capacity was 100.1 mAh g. -1 After 10,000 cycles, the capacity retention rate was 83.2%.

[0130] (4) Example 4: In 0.1Ag -1The discharge specific capacity at current density is 277.4 mAh g. -1 In 5Ag -1 Under long-cycle charge-discharge testing, the initial specific capacity was 94.3 mAh g. -1 After 10,000 cycles, the capacity retention rate was 85.4%.

[0131] (5) Example 5: In 0.1Ag -1 The discharge specific capacity at current density is 293.4 mAh g. -1 In 5Ag -1 Under long-cycle charge-discharge testing, the initial specific capacity was 107.6 mAh g. -1 After 10,000 cycles, the capacity retention rate was 85.2%.

[0132] (6) Example 6: In 0.1Ag -1 The discharge specific capacity at current density is 275.1 mAh g. -1 In 5Ag -1 Under long-cycle charge-discharge testing, the initial specific capacity was 74.2 mAh g. -1 After 10,000 cycles, the capacity retention rate was 78.4%.

[0133] (7) Comparative Example 1: In 5Ag -1 The following long-cycle charge-discharge test was conducted. Figure 6 The initial discharge specific capacity is 72.8 mAh g. -1 After activation, the specific capacity increased to 94.5 mAh g. -1 After 10,000 cycles, the specific capacity is 62.9 mAh g. -1 .

[0134] (8) Comparative Example 2: In 5Ag -1 The following long-cycle charge-discharge test was conducted. Figure 7 The initial discharge specific capacity is 70.0 mAhg. -1 After 5500 cycles, the specific capacity was 49.6 mAh g. -1 .

[0135] (9) This invention further investigated the effect of vanadium pentoxide concentration regulation on the phase structure and crystallinity of the product; in solution A, when the vanadium pentoxide concentration is controlled within the range of 0.04–0.07 mol / L, it is easier to form a pure phase of H. 11 Al2V6O 23.2 The pure-phase layered structure, with its moderate interlayer spacing, is beneficial for Zn. 2+Intercalation / deintercalation and ion diffusion are crucial for improving rate performance. Too low a concentration (<0.03 mol / L) may result in insufficient reactant participation and incomplete formation of the product structure, affecting its specific capacity and cycle stability. Conversely, too high a concentration (>0.1 mol / L) may lead to the formation of byproducts or agglomerates, increasing particle size, restricting ion migration channels, and thus reducing battery performance. Data from the examples show that under vanadium pentoxide concentrations of 0.04–0.07 mol / L, the prepared material exhibits good performance at high current densities (5 A·g⁻¹). -1 The material exhibits excellent long-cycle performance (>85% capacity retention, 10,000 cycles), indicating that control within this range is beneficial for achieving a good balance between structural stability and conductivity. Therefore, the selection of different concentrations of vanadium pentoxide directly relates to reaction kinetics, material structure, and electrode interface properties, ultimately significantly affecting the material's specific capacity, rate performance, and cycle life.

[0136] In conclusion:

[0137] All examples exhibited excellent specific capacity and cycle stability, with the specific capacity maintained between 275.1 and 378.4 mAh g⁻¹. -1 Between these two examples, the capacity retention rate remained stable at over 75% after 10,000 cycles under high current density conditions; while Comparative Examples 1 and 2 were significantly inferior to the example in both aspects. This also demonstrates that the design strategy of the present invention is feasible and effective, forming a pure phase H by precisely controlling the Al / V molar ratio. 11 Al2V6O 23.2 The layered structure, with its expanded interlayer spacing, effectively enhances zinc ion diffusion kinetics and structural stability. The GaIn alloy constructs a conductive network within the electrode, reducing interfacial impedance and buffering cyclic volumetric strain to suppress active material shedding. Experimental results show that this co-doped material maintains excellent capacity output even at high current densities, exhibiting almost no capacity decay after tens of thousands of charge-discharge cycles, demonstrating significantly superior performance compared to traditional vanadium-based materials.

[0138] Furthermore, the hydrothermal synthesis method employed in this invention features a simple process flow, widely available raw materials, and is environmentally friendly. It avoids the safety and environmental risks associated with traditional high-temperature calcination or organic solvents. The preparation process is highly controllable, suitable for mass production and engineering scale-up, and possesses excellent practical application potential. More importantly, GaIn-HAVO cathode materials are not only suitable for aqueous zinc-ion batteries but can also be widely applied to various novel ion battery systems such as lithium, sodium, and magnesium. They hold significant value in multivalent ion energy storage research and the development of green energy storage systems, demonstrating broad prospects for industrial application.

[0139] Finally, it needs to be explained that the above examples are only used to illustrate the technical solutions of the present application but not to limit the technical solutions, and those of ordinary skill in the art should understand that the technical solutions of the present application are modified or equivalently replaced without departing from the purpose and scope of the technical solutions, which should be covered in the scope of claims of the present application.

Claims

1. A method for preparing a gallium-indium alloy-doped aluminum vanadium oxide hydrate positive electrode, characterized in that, The method comprises the following steps: Step 1: Vanadium pentoxide is added into ethanol solution to obtain solution A; In the solution A, the concentration of vanadium pentoxide is 0.03-0.1 mol / L; Step 2: H2O2 is added into the solution A in step 1, and the reaction is continuously stirred to completely pyrolyze the vanadium pentoxide; wherein the amount of H2O2 added in 1 g of vanadium pentoxide is 3-7 mL; Step 3: Aluminum chloride is added into ethanol solution to obtain solution C; in the solution C, the concentration of aluminum chloride is 0.05-0.2 mol / L; Step 4: The solution C is added into the solution B, and the stirring is continuously carried out for 2-4 hours to obtain solution D; wherein the volume ratio of the solution C to the solution B is 1: (2-5) ; Step 5: The solution D obtained in step 4 is reacted at 160-200 ℃ for 12-35 hours, and the reaction product is obtained after being naturally cooled and filtered; Step 6: The reaction product filtered in step 5 is washed and dried for multiple times to obtain aluminum-doped hydrated V2O5 powder; the aluminum-doped hydrated V2O5 powder, conductive carbon black and polyvinylidene fluoride are uniformly mixed, and N-methyl pyrrolidone is added to form a slurry; wherein the mass ratio of the aluminum-doped hydrated V2O5 powder, the conductive carbon black and the polyvinylidene fluoride is 7:2:1; Step 7: A gallium-indium alloy dispersion liquid is added into the slurry obtained in step 6, and the slurry is sufficiently ground, and then the obtained slurry is coated on a current collector to obtain the positive electrode after being dried.

2. The preparation method according to claim 1, characterized in that, In the solution A in step 1, the concentration of vanadium pentoxide is 0.04-0.07 mol / L.

3. The preparation method according to claim 1, characterized in that, In step 2, the amount of H2O2 added is 4-6 mL of H2O2 per 1 g of vanadium pentoxide; according to the mass percentage, the concentration of H2O2 is 30%.

4. The preparation method according to claim 1, characterized in that, In the solution C in step 3, the concentration of aluminum chloride is 0.08-0.15 mol / L.

5. The method of claim 1, wherein the step of forming the first and second layers is performed by a process selected from the group consisting of: sputtering, evaporation, and chemical vapor deposition. In step 5, the reaction temperature is 180 ℃, and the reaction time is 24 hours.

6. The method of claim 1, wherein the step of forming the first and second layers is performed by a process selected from the group consisting of: sputtering, evaporation, and chemical vapor deposition. In step 7, the grinding time is 10-15 minutes, and the current collector is a metal titanium foil; the gallium-indium alloy dispersion liquid is obtained by the following steps: The gallium-indium alloy is added into ethanol, and is broken for 5-10 minutes to obtain the gallium-indium alloy dispersion liquid; wherein 3 μL of the gallium-indium alloy is prepared with 1 mL of ethanol.

7. Use of a positive electrode prepared by the production method according to any one of claims 1 to 6, characterized in that, The positive electrode is used for a water-based zinc ion battery.

Citation Information

Patent Citations

  • Aqueous zinc ion battery vanadium-based positive electrode material and preparation method and application thereof

    CN111573731A

  • Preparation method and application of vanadium-based positive electrode material of aqueous zinc ion battery

    CN112635746A